Recombinação, inspiração e fluxo: a série animada FLCL e uma cartografia das imagens - Moura, Luiz Armando de (2021)
This work studies the field of relationship between the viewer and a work of art, mainly based on the Japanese animation FLCL (2000), created by Kazuya Tsurumaki, which to this day continues to be discussed and consumed by people all over the world. New theories, interpretations and discussions continue to emerge as time goes by in all cultural environments. The guiding thread of the research is the animated television series, but we use frequent splashes in other works of art: Other animations; experimental films; cinematographic adaptations of literature and more experimental forms of audiovisual media remix, such as Anime Music Videos and Youtube Poop, in order to find commonalities in the audiovisual language to navigate the environment of these images. As a tool, we used Vilém Flusser's theory about images produced by electronic devices, and his theory about the writing of cinematographic script, production and consumption of audiovisual. We also used the concept of pathosformel proposed by Aby Warburg as developed by Norval Baitello Junior and Christoph Wulf, in order to compose a cartography of the images, and we traced an analysis of FLCL and the Gainax Studio, where the anime was made. Here we use as a tool the writings of Dani Cavallaro, an interview with Hideaki Anno, articles on Cinema by critics Roger Ebert and Yuan Qingfeng and texts of literary analysis. Finally, considerations about nostalgia and revivals are made with Julio Plaza's Intersemiotic Translation studies. We also study the means, techniques and processes that stimulate the flow of images and, thus, propose a way of analysis and creation of an Art that escapes binary movements of exclusion and opposition, encouraging combination, translation and confluence. Above all, this dissertation intends to propose a happy way, and therefore not less demanding or attentive, to carry out such studies and to draw a cartography of the images - above all of the techno-images - wide and easy to navigate